E-Book Berbasis AR dengan CBL SDGs : Meningkatkan Literasi Keuangan pada Siswa Sekolah Dasar - Mukhlis, Septian; Kurnia, Ira Restu; Syahwildan, Muhamad; Sulistiawati, Nika; Kenju, Rifa Naila Meiliani Manoppo (Action Research Journal Indonesia (ARJI), 2025)
Financial literacy is a crucial life skill that must be developed from an early age, yet Indonesia’s financial literacy index remains relatively low despite broader access to financial services. This study examines the effectiveness of an Augmented Reality (AR)-enhanced e-book integrated with Challenge-Based Learning (CBL) and Sustainable Development Goals (SDGs) in improving financial literacy among elementary students. A total of 240 fourth-grade students from four public schools participated in a mixed-methods design, divided into experimental and control groups. Data were collected through pre- and post-tests, questionnaires, interviews, and observations. Results showed that the experimental groups achieved higher post-test scores and medium N-Gain values (0.45–0.49), whereas the control groups remained in the low category (0.19–0.22). Statistical analysis further confirmed significant treatment effects, with Group factor values ranging from F = 16.72–20.08; p < .05, indicating that improvements were attributable to the AR-based intervention rather than initial ability differences. The Pre-test factor also showed significance (p < .05), yet the intervention demonstrated a stronger influence, supported by moderate-to-large effect sizes (Partial η² = 0.22–0.26). The study concludes that AR-based CBL–SDGs e-books effectively enhance financial literacy and foster meaningful learning experiences in primary education.